(untitled) (Comprehensive Journal of Science, 2025)
The elemental content of two herbs, Salvia officinalis and Polygonum equisetiforme, grown in Libyan wilderness was analysed using four different digestion methods for sample preparation. the samples. The elements which determined in these plants were Ca, Mg, Na, K, Fe, P, Si, Mn, Zn, Cu, Co, Ni, Cr, Al, Hg, Pb and Cd, measured by ICP-AES technique. The macronutrients Ca, Mg, K, Na, P and Fe represent the highest concentrations in these samples ranging from Ca which owns the highest continent to Fe with the lowest concentration. The result also exhibits the highest micronutrient composition was detected for Si, Mn and Zn respectively. The toxic element, Al, was found at high level compared to other toxic elements which could be related to environmental content. Statistical analysis (PCA, PLS-DA and HCA) data reveal that there are significant differences between water extraction method and other digestion methods. These differences could be explained by the ability of water to extract soluble salts only. Meanwhile there is a slight difference between ashing procedure and other digestion methods HNO3/H2O2 and HNO3/HClO4 methods). The results also show significant difference in terms of elemental content. For example, the samples have significant differences in the concentrations of Mn, Cu and Ni. While no significant differences were observed in the concentrations of Cr and Sn.